ANALISIS PENERAPAN MATERIAL REQUIREMENTS PLANNING (MRP) DALAM UPAYA MENGENDALIKAN PERSEDIAAN BAHAN BAKU KNALPOT Pada UD. Bengkel GRM (Gandhoel Racing Modification) Tuban - M. Ali Sukamto; Muhammad Hufron; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACK The purpose of this research is to know whether the application of MRP method or Material Requirements Planning can attempt to control the supply of raw material exhaust at UD. GRM Workshop (Gandhoel Racing Modification) Tuban. After the calculation of the analysis of the application of Material Requirements Planning method, it is known that the requirement planning and the raw material purchase schedule have been done correctly, ie at the final production process stage, during the six sets of finished exhaust products produced in the 4th week of January (period 4) the 3rd of February (period 7) 2018.Then for the result of inventory control of raw material two lot sizing technique obtained that Lot lot lot technique (LFL) yield optimal lot size from Part Period Balancing (PPB), caused by lot lot lot technique of raw material inventory cost on plate is Rp 2.233 .350 Step Period Balancing (PPB) is Rp. 2,997,476. and raw materials of aluminum pipe and electrode in two lot sizing techniques produce the same total inventory cost, for aluminum pipe is Rp 1.459.400 and electrode is Rp. 1.69.400. Keywords: Material Requirements Planning, inventory control, lot sizing, Lot fot lot (LFL) and Part Period Balancing (PPB)